IMPROVING STUDENTS’ VOCABULARY COMPREHENSION IN LEARNING ENGLISH THROUGH PICTURES - Marni Bawawa; Sri Winarsih (Universitas Musamus Merauke, 2020)
The objective in the research are to find out whether teaching vocabulary through pictures can improve the students’ vocabulary comprehension, and are the students’ interest in learning vocabulary through pictures at SMP Negeri 3 Merauke and the subject in this research was eight grade students B and C in SMP Negeri 3 Merauke. The research method using divided into quasi-experimental research. This sample of the research consisted of 40 students divided into two groups namely: 20 students to experimental group and 20 students to control group and conclude the data using two instruments; the vocabulary test for the students’ vocabulary achievement was analyzed used SPSS and the questionnaire was used to see students' interest in English learning vocabulary. To the result indicated that the through pictures media improves the vocabulary of the eight grade students in SMP Negeri 3 Merauke. It was proven by the mean score of posttest of experimental group which higher than the mean score of control group in vocabulary test (81.5>51.7) and the difference was statistically significant based on the result of the t-test of posttest indicated the probability value is smaller than alpha value (0.00<0.05). It means that, the use of pictures media was more effective to improving students vocabulary comprehension of the eight grade Students of SMP Negeri 3 Merauke than without using pictures media and the students also more interested in learning English vocabulary by using picture media than without using pictures media. As indicated by the results score of the questionnaire, namely there were twelve students or 60% to score are the strongly interested classification and eight students or 40% are the interested classifications. It means that, most of the students were interested in English learning vocabulary through pictures media in learning process. Keywords: improving; vocabulary; comprehension; pictures